Simultaneous electrochemical detection and determination of lead and copper at boron-doped diamond film electrodes - Prado, C; Wilkins, S; Marken, F; Compton, R (2002)
Boron-doped diamond (BDD) was used as solid electrode material for the simultaneous detection of trace lead and copper in solution using anodic stripping voltammetry (ASV). Peaks due to Cu and Pb were identified and the conditions under which independent measurements of each can be undertaken are delineated. Voltammetry and AFM imaging is used to show that while both metals nucleate as their pure phases on BDD, once formed the copper nuclei act as favorable sites for the subsequent nucleation and growth of lead; the latter act inhibiting hydrogen evolution on the copper surface. However under stripping conditions, as the lead is preferentially oxidized, an extra peak due to hydrogen evolution at freshly exposed copper appears in SWV experiments. Nevertheless, ASV at BDD electrodes provides the basis for a method of independent detection of Cu and Pb via conventional standard addition procedures.